Tomato plant production in NTB per year using Single Exponential Smoothing (SES) Method - Putri, Dwi Noorma; Febrilia, Baiq Rika Ayu; Anggraeni, Dara Puspita (Universitas Muhammadiyah Mataram, 2023)
Tomatoes are one of the horticultural crops that many people use for consumption in everyday life. Because tThe demand for tomatoes is quite large, but sometimes the availability is too little or too much, it is necessary to study the changing trends or movements in tomato production each year. This research aims to predict tomato plant production in West Nusa Tenggara (NTB) Province, using the Single Exponential Smoothing (SES) method by observing several α values. The best α value is selected by looking at the smallest MAPE (Mean Absolute Percentation Error), MAD (Mean Absolute Deviation) and MES (Mean Square Error).Those value values is considered to give the best model.The data was taken from BPS from year 2011 to 2022This research aims to predict tomato plant production in West Nusa Tenggara (NTB) Province using the Single Exponential Smoothing (SES) method by observing several α values. The research object taken in this research is data on the number of tomato plant production from 2011 to 2022 in West Nusa Tenggara (NTB) Province. The research object taken in this research is data on the number of tomato plant production from 2011 to 2022 in West Nusa Tenggara (NTB) Province. Data was analyzed manually using Microsoft Excel. The best α value is selected by looking at the smallest MAPE (Mean Absolute Percentation Error), MAD (Mean Absolute Deviation) and MES (Mean Square Error) values. The research results show that the value α =0,1 is the α value with the smallest MAPE, MAD and MES values. Therefore, for tomato production data from 2011 to 2022 in NTB Province, the best forecasting model using the SES method is given by α =0,1.